RESILIENSI SINGLE MOTHER YANG MEMILIKI ANAK DISABILITAS INTELEKTUAL - Fatimah Azzakiyah; Rona Ghina Luqyana; Della Puteri Anggraeni; Faradhila Berliana Putri (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The purpose of this study was to demonstrate how resilience works in mothers who care for children with intellectual disabilities. To study the participants' experiences comprehensively, a qualitative approach involving case studies was used. Three participants were selected through purposive sampling based on the criteria of being single mothers who had children with mild, moderate, or severe intellectual disabilities. Thematic analysis was used to collect data after semi-structured interviews. The results of the study showed that when participants received their children's diagnoses, they experienced an initial emotional phase of shock, denial, stress, and confusion. Emotion regulation, impulse control, optimism, problem-solving skills, empathy, self-efficacy, and self-achievement are factors of resilience. Cognitive, emotional, spiritual, behavioral, and social strategies are used for adaptation. The resilience process is highly dependent on family, community, therapy, and disability community support. In conclusion, resilience enhances mothers' adaptive abilities, parenting stability, and psychological well-being. This study improves our understanding of the psychological resilience of parents raising children with intellectual disabilities and builds solutions for family support.